PENGARUH KESEHATAN DAN KESELAMATAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PT BETON PERKASA WIJAKSANA CABANG MAKASSAR - Arfiany, Arfiany; Citta, Andi Batary (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2018)
In the new paradigm will be reflected the new work culture, strategy and role of human resources from within the typology of the new organization. The industrial world is growing. The development of the industry can not be separated from the advancement in the field of technology. Technology almost sets aside the human workforce, however labor is always needed. PT Beton Perkasa Wijaksana Makassar Branch is one of the companies engaged in producing concrete. Although the duties of each employee are very different from each other, but inter depending on each other, must work together and also have to fill each other in order to achieve the individual goals of employees as well as the goals of groups or organizations. To support the ease of achieving these goals, employees both individually and required to continuously make improvements or improve the quality of themselves or their groups.The study aims to identify how influential employees' occupational health and safety is so that it affects their productivity. Sampling in this study was used by 102 respondents, the data collection technique is by questionnaire, research variables are Health (X1), Safety (X2), Productivity (Y). The data was tested for validity using Pearson Product Moment correlation and to test its reliability level using Cronbach Alpha and then the data was processed with Multiple Linear Regression Analysis. Hypothesis Testing using F and T Tests with a level of 5% significance. Keywords: Occupational Health, Safety and Work Productivity.